Lead Content and Isotope Composition in Surface Sediments in Western Xiamen Bay and Its Vicinity: Implication for Possible Source - Hu, X.; Ding, Z.; Liu, X.; Yao, F.; Lian, H. (Asian Journal of Chemistry, 2013)
Lead contents and isotope compositions (206Pb/207Pb and 208Pb/206Pb) in surface sediments in western Xiamen Bay and its vicinity in South Fujian, China, were measured to assess the spatial variations and to identify Pb sources. The spatial variations of Pb contents in sediments were confirmed and enrichment factors suggested deficiency to minimal enrichment of anthropogenic lead in sediments. Lead isotopic ratios ranged from 1.173-1.186 with the mean value of 1.181 for 206Pb/207Pb and from 2.078-2.101 with the mean value of 2.094 for 208Pb/206Pb, respectively. The Pb isotope ratios indicated the homogenization of isotope compositions and confirmed that vehicular Pb was not the primary Pb contamination sources in the sediments in the studied region. Chinese coal and Fujian Pb-Zn deposits might be the potential anthropogenic Pb sources and Fujian basalts and granite are the important natural Pb source.